ERAN PEMERINTAH DESA DALAM PEMBERDAYAAN MASYARAKAT NELAYAN DI DESA KOJA DOI - SARIF; DANAR ASWUN; PETRUS KPALET (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
This study aims to describe 1) the role of the village government in empowering fishing communities by the government of Koja Doi Village, East Alok District, Sikka Regency 2) What are the obstacles that affect the empowerment of fishing communities in Koja Doi Village, East Alok District, Sikka Regency. This research is a qualitative research. The subjects of this stuKdy were the Koja Doi Village Government and the Koja Doi Village Fisherman Society. Data collection techniques were carried out through interviews, observation and documentation. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of the study indicate that 1) The role of the government in Koja Doi Hamlet has effectively carried out its duties as the government, especially the Fisheries and Marine Service, where the government has provided sufficient assistance to the fishing community in Koja Doi Hamlet such as group assistance from catonic nurseries, fishermen’s assistance such as machines, boats, and fishing nets, but not all fishing communities get this assistance 2) Constraints to the Government’s Efforts in Empowering Fishermen Communities, Budget constraints are one of the important factors in implementing the fishermen empowerment program in Koja Doi Village. Because the budget is a driving factor for the smooth running of all elements of government institutions